Kewenangan Mahkamah Konstitusi Dalam Perlindungan Hak Konstitusional Warga Negara Melalui Konstitusional Complaint - Benito Asdhie; Eza Ista (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
The constitutional court brought Indonesia towards a better democracy. This is due to the existence of a separate institution that specifically safeguards the dignity of the 1945 Constitution of the Republic of Indonesia as the highest norm in Indonesia, so that any actions related to the constitution can be responded specifically to the constitutional court. In addition, the position of the constitutional court in the state institutional structure as an institution that is equal to the people's consultative assembly, the house of representatives, the regional representative council, the president, the supreme court and the judicial commission has affirmed that the constitutional court is an institution that has high authority in the corridors of its authority. The research is a basic tool in the development of science and technology. This is because research aims to express the truth systematically, methodologically, and consistently. Through the research process analysis and construction of data that has been collected and processed is conducted. the problem in this research is how is the concept of constitutional complaints as a form of protection of citizens' constitutional rights, how is the alternative application of constitutional complaints authority in Indonesia. The result of this research is that constitutional complaints are one of the defense mechanisms for citizens to defend their constitutional rights through the courts against the exercise of state power.